2022
DOI: 10.1039/d1fo04085e
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of taurocholic acid on excessive hepatic lipid accumulationviaregulation of bile acid metabolism in grouper

Abstract: Dietary bile acids (BAs) supplementation can notably ameliorate the fatty liver disease caused by high dietary lipids, but the mechanism behind this is poorly understood. The present study was aimed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Since fish can synthesize cholesterol, it is usually considered a non-essential nutrient [ 39 ]. Liver is the principal site of cholesterol synthesis, as well as the place of producing bile acids by cholesterol, where HMGCR and CYP7A1, CP27A1 are the key enzymes involved in cholesterol synthesis and bile acid production, respectively [ 40 ]. The farnesol X receptor (FXR) is the bile acid receptor that inhibits the expression of cyp7a1 to negatively regulate the production of bile acids [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since fish can synthesize cholesterol, it is usually considered a non-essential nutrient [ 39 ]. Liver is the principal site of cholesterol synthesis, as well as the place of producing bile acids by cholesterol, where HMGCR and CYP7A1, CP27A1 are the key enzymes involved in cholesterol synthesis and bile acid production, respectively [ 40 ]. The farnesol X receptor (FXR) is the bile acid receptor that inhibits the expression of cyp7a1 to negatively regulate the production of bile acids [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…( Long et al, 2017 ). In turn, BAs are crucial players in modulating the composition of gut microbiota ( Xu et al, 2022 ). Targeting the gut microbiota–BA axis may be a promising therapeutic strategy for liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that dietary supplementation with BAs can significantly improve the growth performance and maintain glucose and lipid metabolism homeostasis in largemouth bass (Micropterus salmoides) and hybrid grouper (Epinephelus fuscoguttatus × E. lanceolatus). 52,53 In addition, dietary supplementation with UDCA and LCA significantly improved hyperlipidemia and hepatic steatosis in ob/ob mice. 27 Taken together, our study implies that B. cereus Su1 may improve the metabolic disorders induced by the HCD by altering the BA profile in the gut and liver.…”
Section: Discussionmentioning
confidence: 99%